Conceptualizing Human Capital As A Free-Exploitation Instrument In Economic Development - Ign Heri Satrya Wangsa (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2009)
Human capital with in the context of economic development means efforts to revitalize meaning of development which is more on developing economic capacity for human within the concept of homo economicus. It means that, the appropriate meaning of economic development is to replace pt of human as an economic man who is free from exploitation. Economic development should be directed at human as potential resources which contribute to productivity. Therefore, within the context of economic development, the concept of homo economicus should be clearly defined as human who recognizes himself consciously as economic man and economic instrument as well. Consequently, it is necessaery to create and develop economic values potensials to increase productivity. Process of human capital accumulation which consciously accomplished has placed human as subject in economic development. Facts of capitalism has reduced and minimized human as resources that run a risk of exploitation. The human dimension in economic development should be directed to the concept of homo economicus perceived as “human who is completely conscious” and a free-exploitation resources.